Typical dreams of falling, being chased, and being paralyzed in Germany from 1956 to 2000 - Schredl, Michael (International journal of dream research, 2021)
Typical dream themes like falling, being chased, and being paralyzed are very common in many different cultures and time epochs and are, therefore, also termed universal. The present analyses included data from 4 independent, representative surveys carried out from 1956 to 2000 in Germany. Overall, 5941 participants reported as to whether they had falling dreams, dreams of being chased or being paralyzed. The most frequent topic was being paralyzed; about 26% of the sample reported this dream theme, followed by falling (18%), and being chased (12%). There were no differences between the studies and between age groups. Solely, a small but significant gender difference was found. The findings indicate the stability of these typical dreams, and future study should focus on their details, e.g., the chasing figures, as these might reflect cultural backgrounds. Moreover, it would be interesting to relate the occurrence of typical dream themes to waking-life emotions in order to test the idea that these dreams are metaphorical and dramatized expressions of emotions experienced in waking life.
Gesehen am 19.04.2021